Da previsão do tempo às catástrofes: os valores-notícia dos acontecimentos climáticos no jornal Zero Hora (RS) - Rubin, Anaqueli (2011)
In this study we aim to analyse the role of journalism in creating certain representations of the relationship between man and climate, especially concerning the climate change scenario. We assume that the news is a specific type of symbolic system and configures itself in a cultural construction built through the news values that work with maps of representation. Our main goal is to analyse the climate in Zero Hora, in its various editorials, based on news values to show how it happens in the news the relationship between man and climate. The specific objectives of the research focus on characterizing climate events for journalism, defining concepts such as weather and climate, to understand historically how the relationship between the media and climate and between journalism and meteorology. We present a mapping of climate events in Zero Hora through a quantitative survey of however qualitative approach to identify news values and their meanings based on certain aspects from the theory of Representations using contributions from Patrick Charaudeau, Stuart Hall and Cristina Ponte. We also conducted interviews with professionals in meteorology and journalism field in order to understand how they interact with the subject. Our study aimed to cover from the news that involve the variable weather in the day-by-day life up to the ones that deal with long term climate changes. This was sourced from the newspaper Zero Hora, in Rio Grande do Sul. We analysed 41 editions and mapped the coverage of 90 climate events. Considering the news values found, an observation can be concluded on how Zero Hora represents the relationship between men and climate. This study concludes that the newspaper represents man as a victim of the climate events. Furthermore there is a personification of the nature in these events, in which it is identified as a major culprit for the consequences, changes, destruction and death. This representation of the climate shows that there is no deep discussion over the influence of human intervention on nature itself. The news values that guide the approach to climate and weather in Zero Hora are not related to aspects such as environmental issues. Problems such as poor urban space planning, the siltation of rivers, high risk areas public policies, which can be considered as causes of flooding, for example, are not made evident in the news about the climate.